Seroprevalence of toxoplasmosis among AIDS patients in Hospital Kuala Lumpur, 2001 - Nissapatorn, V.; Lee, C.K.C.; Khairul, A.A. (Stamford Publishing, 2003)
Four hundred and six AIDS patients were recruited in this retrospective study. The seroprevalence of toxoplasmosis among 406 AIDS patients was 208 (51.2). Their age ranged from 17 to 74 years with a median of 35 years. The majority of patients were males 172 (82.6), Malays 99 (47.5), single 109 (52.4), unemployed 99 (47.6) and heterosexual with commercial sex workers (CSW) 97 (46.6) as the risk marker to HIV infection. Thirty-one (14.9) of 208 AIDS-related toxoplasmosis were diagnosed as active toxoplasmic encephalitis. The most common clinical manifestation was headache (67.7). The CT scan findings showed most lesions to be multiple (87.5), hypodense (66.7), and in frontal region (41.7). Twenty-two (71) patients had chronic (latent) Toxoplasma infection as evidenced by seropositivity for anti-Toxoplasma (IgG) antibody. They were statistically significant in the association between CD4 count and toxoplasmic encephalitis (P = 0.019; OR = 2.6; 95 CI = 1.14-6.02). After the initial six weeks of anti-TE therapy, relapsing toxoplasmic encephalitis was detected in 9.7 in this study.